Sosialisasi Daur Ulang Sampah dan Pembuatan Kompos kepada Masyarakat MAN Sidoarjo dan SMK Al-Aziziyah Candi Sidoarjo - Lestari, Heni; Putri, Safira Adelia; Fitrianah, Listin; Irfanudin, Achmad Ali; Maulana, Micola Miftach; Usada, Untung; Sumiyarsono, Elmi; Efendi, Ma'ruf; Mas'ud, Muchamad Ali; Prayoga, Renaldy Dimas; Yusuf, Mochammad; Aditya, Muhammad Zaki; Syah, Aly Mulid (Universitas Nahdlatul Ulama Sidoarjo, 2024)
Organic waste can be reprocessed into compost. Compost can be made using several methods. One composting method is the Takakura method. This method has advantages compared to other methods, namely 1) it is practical, does not require a large location, the basket can be placed anywhere as needed, 2) it is easy because the waste is only put and buried in the composter, 3) it does not smell, because the process is through fermentation, not rotting. The aim of holding this training is to increase students' knowledge and skills in managing organic waste into compost so that they can reduce the amount of waste and create a cleaner andhealthier environment. The activities carried out include socializing waste sorting and making compost, handing over trash bins, making compost, maintaining compost, applying compost to planting media and monitoring the results of compost applicationto planting media.